Successive maturation and senescence of individual leaves during barley whole plant ontogeny reveals temporal and spatial regulation of photosynthetic function in conjunction with C and N metabolism - Wiedemuth, Konstanze; Grzam, Anke; Hell, Rüdiger (Journal of plant physiology, 2005)
During ontogeny of barley plants (Hordeum vulgare, L. cv. Barke), a continuous developmental gradient of new leaves at the top and lower leaves undergoing senescence is maintained. In the course of senescence, specific recycling processes efficiently transfer valuable resources, e.g. nitrogen and carbon, to the growing young leaves and ears. In order to understand the temporal and spatial sequence of processes underlying this developmental program of leaf formation and degradation, changes in photosynthetic parameters, as well as C and N levels of all individual leaves were determined. During whole plant ontogeny, a strict sequential pattern of incorporation and degradation of C and N resources in the individual leaves, accompanied by a sequential loss of chlorophyll and photosynthetic function, was observed. In addition, protein levels of key enzymes of C and N anabolism AGPase (ADPglucose pyrophosphorylase) and GS (glutamine synthetase; plastidic isoform) also showed a strict pattern of sequential down-regulation in senescing leaves. Their decline preceded the breakdown of chlorophyll, total C and N levels and photosynthetic performance in the leaves. Quantitative real time PCR measurements revealed that the down-regulation of protein content of AGPase and GS correlated with a drastic decrease in their transcript levels. These data elucidated precise temporal and spatial regulation of C and N metabolism and allocation with photosynthetic function in the leaves during whole plant ontogeny of barley.
Gesehen am 08.05.2017